Triangular Plasty of Left Atrium in Surgical Treatment of Left Atriomegaly - V. Boukarim; B. N. Gumeniuk; V. V. Popov (Ukrainian Journal of Cardiovascular Surgery, 2020)
Aim. The aim was to determine the possibilities of left atrium (LA) reduction by triangular plasty of LA (TPLA) during mitral valve replacement (MVR). Isolated surgical correction of mitral defect (mitral valve replacement or plasty [MVP]) in the presence of uncorrected left atriomegaly is associated with the long-term manifestation of heart failure with the risk of thromboembolic complications and the absence of reversion to sinus rhythm. The treatment outcomes in patients with isolated mitral defect and left atriomegaly, who were undergoing surgical treatment at the Department of Surgery of Acquired Heart Defects of the Institute were analyzed. The analyzed group included 137 patients. All the patients underwent MVP combined with the original technique of triangular plasty of LA. Among 137 operated patients, 3 (2.2%) died. The changes in echocardiographic parameters at the treatment stages were as follows: LV ejection fraction 0.51 ± 0.05 (preoperative), 0.54 ± 0.05 (postoperative), and 0.56 ± 0.05 (remote). The LA diameter (mm) was 65.5 ± 3.8 (preoperative), 51.5 ± 2.1 (postoperative), and 52.5 ± 2.2 (remote). The technique is less traumatic and outlines an effective procedure which leads to a significant improvement in the LA morphometry and is accompanied by a low risk of hospital mortality.Materials and methods. From 1.10.2010 to 1.01.2019, 137 adult patients (pts) with mitral valve disease (MVD) and giant LA (¤60 mm in diameter) underwent surgical intervention at the Institute. MVR was performed in all the pts. TPLA including ligation of LA auriculum was performed in all the pts. All operations were performed with cardiopulmonary bypass and moderate hypothermia with crystalloid cardioplegia.Results. There were 3 hospital deaths. Echocardiography showed that LA diameter (mm) was 65.5 ± 3.8 (preoperative), 51.5 ± 2.1 (postoperative), and 52.5 ± 2.2 (remote).Conclusions. TPLA during isolated MVR to improve LA morphometry during the postoperative period.